2022
DOI: 10.1039/d1cc06170d
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed coupling of benzyl bromides with BMIDA-substituted N-tosylhydrazones: synthesis of trans-alkenyl MIDA boronates

Abstract: A palladium-catalyzed stereoselective synthesis of alkenyl boronates from N-methyliminodiacetyl boronate (BMIDA)-substituted N-tosylhydrazone and benzyl bromides is developed. A range of trans-alkenyl MIDA boronates as single stereoisomers were obtained in moderate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The inherent instability of α-boryl diazo compounds, 21 arising from the strong Lewis acidity of the boryl group, encumbers their general employment as carbene precursors. 22,23 Recent developments have seen the advent of protocols for gold-mediated transfer reactions involving αboryl carbenes, but these have largely been confined to intramolecular reactions (Scheme 1c). 24 In this context, we identified pinacolatoboryl (Bpin)-substituted cyclopropenes as 13,25−27 Building on this foundation, we introduce a methodology utilizing 1-borylcyclopropenes as precursors for Bpin-substituted metal carbenes, a process efficiently catalyzed by a copper complex.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The inherent instability of α-boryl diazo compounds, 21 arising from the strong Lewis acidity of the boryl group, encumbers their general employment as carbene precursors. 22,23 Recent developments have seen the advent of protocols for gold-mediated transfer reactions involving αboryl carbenes, but these have largely been confined to intramolecular reactions (Scheme 1c). 24 In this context, we identified pinacolatoboryl (Bpin)-substituted cyclopropenes as 13,25−27 Building on this foundation, we introduce a methodology utilizing 1-borylcyclopropenes as precursors for Bpin-substituted metal carbenes, a process efficiently catalyzed by a copper complex.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The Wang group reported a coupling reaction of boryl- N -tosylhydrazones with benzyl bromides under the influence of a palladium catalyst. 20,25 However, these conditions were not operative for our boryl- N -tosylhydrazone 4 . After exploration of reaction conditions, we found that Barluenga's coupling reaction of 4a with p -tolyl bromide in the presence of Pd 2 (dba) 3 , XPhos, and LiO t Bu in 1,4-dioxane 15 produced desired coupling product 5a in 9% as a mixture of E / Z isomers.…”
mentioning
confidence: 95%
“…18 Another example is boryl formyl- N -tosylhydrazone, which reacted under Pd-catalyzed cross-coupling with benzyl bromides to furnish valuable alkenylborons. 19,20 Despite these pioneering works, the structural diversity of the obtained compounds is far from satisfactory. To build a wider range of molecular skeletons, we herein report the development of chloroacetyl boronate N -tosylhydrazone (CABT; Fig.…”
mentioning
confidence: 99%
“…Traditional methods for the radiosynthesis of alkenyl fluoride employed alkenyl stannanes or boronates, which were derived from the aromatic fluoride labeling strategy . Compared to those of aryl stannanes or boronates, the synthesis of similar alkenyl precursors was much more difficult because of the limited stereochemically defined commercial building blocks . The toxicity of organotin reagents and extra steps for the synthesis of precursors limited the broad application of these strategies.…”
mentioning
confidence: 99%